THE USE OF TWENTY QUESTIONS GAME TO TEACH YES/NO QUESTIONS IN SIMPLE PRESENT TENSE - Silaban, Rosalia Jennie A.; ., Sudarsono; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research aims to investigate how effective Twenty Questions Game is to teach yes/no questions in simple present tense to Year-7 students of? SMP Negeri 10 Pontianak? in Academic Year 2014/2015. This research was one of pre-experimental design, namely one group pre-test and post-test design. The sample was a cluster. They were Year-7 Class F, which consisted of 28 students. The tool used for collecting the data was pre-test and post-test. The test was an objective test with multiple choice items. The research findings indicate that the students? mean score in post-test is 94.05 higher than their mean score in pre-test which is 68.92. The effect size of the treatment is categorized as strong, with 1.92 that is larger than 1.00. Therefore, it can be concluded that the use of Twenty Questions Game to teach Yes/No questions in Simple Present Tense to Year-7 students of? SMP Negeri 10 Pontianak? Academic Year 2014/2015 was effective. Keywords: Twenty Questions Game, Yes/No Questions Abstrak: Penelitian ini bertujuan untuk mengetahui seberapa efektif Twenty Questions Game untuk mengajar Yes/No Questions dalam simple present tense pada siswa kelas 7 di SMP Negeri 10 Pontianak Tahun Akademik 2014/2015. Penelitian ini menggunakan pra-eksperimental, yaitu dalam bentuk one group pre-test post-test. Sampel dari penelitian ini adalah sebuah kelompok. Mereka adalah siswa kelas 7F yang terdiri dari 28 siswa. Alat yang digunakan untuk mengumpulkan data adalah pre-test dan post-test. Test tersebut berupa objektif test dengan item pilihan berganda. Hasil dari penelitian,ini mengindikasikan bahwa nilai rata-rata siswa pada post-test sebesar 94.05 lebih tinggi dibandingkan nilai rata-rata siswa pada pre-test yang mana sebesar 68.92. Effect size dari perlakuan dikategorikan sebagai ?kuat?, dengan 1.92 lebih besar dari 1.00. Oleh karena itu, dapat disimpulkan bahwa penggunaan Twenty Questions Game untuk mengajar Yes/No Questions dalam simple present tense pada siswa kelas 7 di SMP Negeri 10 Pontianak Tahun Akademik 2014/2015 adalah efektif. Kata kunci: Twenty Questions Game, Yes/No Questions